Microfluidic single-cell transcriptional analysis rationally identifies novel surface marker profiles to enhance cell-based therapies - Robert C. Rennert (Nature Portfolio, 2016)
Unrecognized progenitor cell perturbations underlying a disease state may limit the efficacy of cell therapies. Here, the authors use high-throughput, single-cell transcriptional analysis to identify disease-specific cellular alterations and prospectively isolate restorative cell subpopulations.